Marble statue of Our Lady of Fatima - Mumbai Archive Project Team (Jio Institute, 2024)
The marble statue of Our Lady of Fatima stands six and a half feet tall, holding a rosary. It was built as a memorial to the Marian Congress held in Mumbai from December 4–8, 1954. Our Lady of Fatima is a title attributed to the Virgin Mary following her apparitions to three shepherd children in Fatima, Portugal, in 1917.